Knowledge Mapping on Maize (Zea mays L) Production Technologies by The Farmers of Karimnagar District in Telangana State (Indian Journal of Extension Education, 2017)
The present paper highlights the knowledge levels of farmers on maize production technologies in Karimnagar district of Telangana State. Ex-post facto research design was adopted for study. Total ninety (90) farmers were selected for study of maize crop knowledge mapping. High level of knowledge of maize production technologies was observed among the KVK Jammikunta adopted farmers compared to the non-adopted farmers.